Effect of Area, Academic Stream and Neurotic Personality Pattern on Human Rights Awareness of Senior Secondary School Students: Exploring the awareness of human rights among senior secondary school students in Himachal Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2018)
To save humanity is to serve God and it has been said by all humanist thinkers. But nowadays newspapers, magazines and other news media are flooded with reports of crime, murder, agitation and ever-teasing deeds against humanity. All these occurrences indicate deterioration in our ethical standards, loss of our moral and social values resulting in great loss to families, society, nation and ultimately the globe at large. Today the human beings are gradually converting themselves from psycho-social to only biological organism, though they are not only a biological organism, but also a psycho-social. We are bearing self-centeredness and this perception towards valuing humanity or human values giving a great thrust on divisive and distinguishing tendency. In that way, ultimately we will be forced the provisions made by our forefather in the Constitution of India, really it is the great source of human values and it looks forward to promote the conducive environment pertaining to humanism. But only having provisions are not sufficient, they should be translated into action by the citizens like ours. This paper highlights the human rights awareness among senior secondary school students of Himachal Pradesh.